Dukungan Sosial yang Diterima dan Konsep Diri Orang yang Terinfeksi Human Immunodeficiency Virus (HIV) di Jaringan Odha Berdaya (JOB) Bandar Lampung - Frisca Kusumawardani; Martha Tifani (Jurnal Genta Kebidanan, 2022)
Physical changes due to the symptoms of the disease caused by a decreased immune system affect the personal, social, study, career and even family life of people infected with HIV. It is known that family support is the most dominant factor related to quality of life. The focus of the researchers explored more deeply about the social support received and the self-concept of people infected with HIV in the Jaringan Odha Berdaya (JOB) Bandar Lampung. This type of research is qualitative with a phenomenological theoretical design. The research has been carried out in the Jaringan Odha Berdaya (JOB) Bandar Lampung. Data collection by in-depth interviews. Data analysis with content analysis. The results showed that all of the informants revealed that they experienced significant weight loss when they were initially infected with HIV. All informants for now have interacted with other people, such as neighbors. Interaction is done after the informant has adapted to his condition. have hope for the future by continuing to carry out daily activities, no longer experiencing hopelessness or depression with HIV because the informant has been able to accept the illness he is suffering from and has received support from his family, Source of support from parents (father/mother) and wife . Forms of support such as reminding time to take medication. become a driver around the informant's house and are motivated in every discussion. Suggestions for families of people infected with HIV can provide good acceptance, provide positive support, and motivation to family members who are indicated to be infected with HIV. It is hoped that the community will not give discriminatory stigma to people infected with HIV.